A Reliability Evaluation Method for Power System with Energy Storage Based on Operation Optimization - Liming ZHANG; Hao LI; Yaxiong WU; Chong GAO; Junxiao ZHANG; Yong LIU (Zhongguo dianli)
In view of the problem that the traditional reliability evaluation method often leads to outage loss of power system, a new reliability evaluation method is proposed for power system with energy storage based on operation optimization. Firstly, a probabilistic model is established according to distributed generation output, and a profit-driven energy storage probability model is established under the peak-valley price mechanism. Secondly, the fault isolation range is refined according to fault types, and the non-fault isolation area is islanded and power matched through network reconfiguration to minimize power outage losses. Finally, a sequential Monte Carlo based reliability evaluation method is proposed. The effectiveness of method is verified through simulation.